Impact of Short-Term Systemic Hypoxia on Phagocytosis, Cytokine Production, and Transcription Factor Activation in Peripheral Blood Cells - Michael Fritzenwanger; Christian Jung; Bjoern Goebel; Alexander Lauten; Hans R. Figulla (Hindawi Limited, 2011)
Hypoxia frequently associated with certain physiologic and pathologic conditions influences numerous cellular functions. Because the effects of short-term hypoxia are incompletely understood, we examined phagocytosis and cytokine production as well as the activation of the transcription factors HIF-1 and NFκB in peripheral blood cells of healthy volunteers exposed to an oxygen concentration equivalent to that found at a height of 5500 m. Furthermore, we analysed plasma HIF-1 and serum concentrations of various HIF-1-dependent genes. Results showed that short-term hypoxia increased phagocytosis in neutrophils without affecting monocyte phagocytosis. Hypoxia decreased basal TNFα concentration in monocytes and basal interferon γ concentration in CD4+ T lymphocytes. In contrast, plasma HIF and serum VEGF concentrations were not affected by hypoxia, although serum EPO concentration was raised. In PBMC, hypoxia increased cytosolic HIF-1 concentration without affecting nuclear HIF-1 concentration and led to a rise in the nuclear NFκB in PBMC. Our results show that short-term hypoxia affects immune functions in healthy individuals. Furthermore, we speculate that the effects of hypoxia are not due to HIF-1, but are caused by the activation of NFκB .